2014
DOI: 10.3892/mmr.2014.2204
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA-26b, an obesity-related microRNA, is regulated by free fatty acids, glucose, dexamethasone and growth hormone in human adipocytes

Abstract: Abstract. MicroRNAs (miRNAs) are short non-coding RNAs that are involved in numerous biological processes, including obesity and insulin resistance. miR-26b is an obesity-related intronic miRNA located in the intron of the carboxy-terminal domain, RNA polymerase II, polypeptide A, small phosphatase 1 gene. miR-26b is abundantly expressed in mice and mature human adipocytes, and is associated with the expression of adipokines. In the present study, the effects of energy-source materials and hormones associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Additionally, visfatin inhibits palmitate-induced apoptosis in pancreatic β-cells [49]. Another finding of the current study was increased survivin levels in response to visfatin which has not been previously investigated.…”
Section: Discussionmentioning
confidence: 44%
“…Additionally, visfatin inhibits palmitate-induced apoptosis in pancreatic β-cells [49]. Another finding of the current study was increased survivin levels in response to visfatin which has not been previously investigated.…”
Section: Discussionmentioning
confidence: 44%
“…Six genes were identified as target genes of miR‐146a and miR‐146b‐5p by overlapping the differentially expressed gene list and predicted target genes using the Targetscan database, namely BCL11A , NUMB , STX3 , KLF7 ), GRID1 , and PBX2 . We examined the expression of these six genes together with tumor necrosis factor receptor‐associated factor 6 ( TRAF6 ) and interleukin‐1 receptor‐associated kinase 1 ( IRAK1 ), two known target genes of miR‐146a, using real‐time quantitative PCR. We confirmed that NUMB , STX3 , BCL11A , and TRAF6 expression was significantly upregulated in patients with newly diagnosed T1D and in those on short‐course (6 months) insulin therapy ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Whether the association between miRNA dysregulation and T1D is dependent on disease duration remains unclear. In addition, interference of hyperglycemia should be excluded because high glucose levels are associated with miRNA dysregulation …”
Section: Introductionmentioning
confidence: 99%
“…Three durations of exposure were used i.e. 4h, 8h and 24 h. After each period of exposure, the cells were harvested and used for further investigations [10,11].…”
Section: Treatment With Adpn Ffas Gh and Dexmentioning
confidence: 99%